A Revised Pedagogy Model for Simulator-Based Training with Biomedical Laboratory Science Students - Björn Marko Henrik; Ravyse Werner; Botha-Ravyse Chrisna; Laurila Jonne M; Keinonen Tuula (MDPI, 2022)
Methods based on simulation pedagogy are widely used to practice hands-on skills in safety environment. The usability of an EEG simulator on clinical neurophysiology course was evaluated. Second-year biomedical laboratory science students (N = 35) on this course were included in the study. They were divided into three groups. Two groups used the EEG simulator with different feedback modes and one group did not use the simulator. Results were expected to reveal a correlation between user experience and learning outcomes. This study made used of a mixed method study design. During the study, students were asked to keep a learning diary throughout the course on their experience. Diaries were analyzed qualitatively based on content analyses. Quantitative analyses based on an UX questionnaire that measures classical usability aspects (efficiency, perspicuity, dependability) and user experience aspects (novelty, stimulation) and the students' feelings to use simulator. The quantitative data was analyzed using SPSSTM software. The quantitative and qualitative analyses showed that the use of the EEG simulator, which was evaluating teaching-learning process, has an extra benefit in clinical neurophysiology education and students felt that the simulator was useful in learning. The simulation debriefing session should be followed by a full theoretical and practical session. Students compared their learning from the simulator with that of the actual placement which fosters the reflective practice of learning, again deepening the understanding of the EEG electrode placement and different wave patterns.